(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Guava is a tropical fruit native to South America. It belongs to the Myrtaceae family and is a well-liked plant. In contrast to other fruits, guava is untreated with chemicals, making it a healthier option. It has long been used as a homoeopathic herb to treat a variety of ailments throughout the globe. Oleanolic acid, tannins, quercetin, ursolic acid, triterpenes, pentacyclic triterpenoid, saponins, carotenoids, amritoside, guajanoic acid, lectins, leucocyanidin, beta-sitosterol and uvaol are among the active components. Guava contains antibacterial, anti-malarial, anti-diarrheal, anti inflammatory, anti-cancer, anti-hyperglycemic, and antioxidant properties, among others. Several studies have revealed that guava contains a number of pharmacological active components that are responsible for a variety of biochemical activities, including antidiabetic, antimicrobial, antidiarrheal, anti-oxidant, anti-pyretic, cardioactive, hepatoprotective, immunomodulatory, spasmolytic, and contractile effects, which are discussed further in the review. This article discusses about pharmacological activities and how they may be used to treat a variety of illnesses and diseases.